PPO.56 A retrospective observational study of second-trimester miscarriage. (9th June 2014) - Morris, A; Meaney, S; Spillane, N; O'Donoghue, K
Abstract : In the UK and Ireland, second-trimester miscarriage is deﬁned as pregnancy loss after the 14th and before the 24th week of gestation. 1 Those who suffer a second-trimester loss represent a small cohort but experience significant morbidity associated with both their index loss and subsequent pregnancies. 1 The literature on this topic, however, is limited. This study aimed to assess maternal characteristics of second-trimester loss. A retrospective observational study of women who experienced a second-trimester miscarriage was undertaken in a large, tertiary hospital (8, 500 deliveries per annum) in the Republic of Ireland. All cases between July 2009 and June 2013 were identified. Charts were reviewed; examining maternal demographics, mechanism of pregnancy loss and inpatient course. During this 4 year period, 173 women experienced a second-trimester miscarriage; with a mean age of 33.59 years (SD:5.46)and mean BMI of 27.09 (SD:6.58). 30.6% were primiparous. 11.4% had previously experienced a second-trimester loss. The average gestation of loss was 17+5 weeks (SD:30 days). 66.3% of losses were intra-uterine deaths with 17.4% following pre-term premature rupture of membranes and 16.3% following preterm labour. 32.4% delivered spontaneously, however 59.5% required medical induction of labour. All patients required inpatient admission with a mean stay of 2.67 days (SD:2.98). 16.9% required oral antibiotic therapy, 8.1% required intravenous therapy and 12.8% requiring both. 26% required manual removal of placenta. Identification of maternal and pregnancy characteristics of second-trimester loss may aid optimisation of risk-stratification and surveillance in future populations, reducing morbidity. Our understanding would benefit from more populous prospective case-control studies. Reference: Edlow AG, Srinivas SK, Elovitz MA. Second-trimester loss and subsequent pregnancy outcomes: What is the real risk? Am J Obstet Gynecol . 2007 Dec; 197(6):581.e1–6